Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1155/2019/3951574
|View full text |Cite
|
Sign up to set email alerts
|

Transient Elastography and Ultrasonography: Optimal Evaluation of Liver Fibrosis and Cirrhosis in Patients with Chronic Hepatitis B Concurrent with Nonalcoholic Fatty Liver Disease

Abstract: Background and Aims. Concordance between transient elastography (TE) and ultrasonography (US) in assessing liver fibrosis in patients with chronic hepatitis B (CHB) and concurrent nonalcoholic fatty liver disease (NAFLD) has been rarely studied. This study aimed to evaluate the individual and combined performances of TE and US in assessing liver fibrosis and cirrhosis. Patients and Methods. Consecutive CHB patients with NAFLD were prospectively enrolled. TE and US examinations were performed, with liver biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Although TE may be affected by several factors, it shows good to excellent performance in CHB patients and decreases the need for LB [13, 27]. Similar to our previous study [28], TE had excellent performance in detecting liver fibrosis and cirrhosis, as revealed by AUCs in the current study. To our knowledge, no comparison between TE and GPR in assessing liver fibrosis and cirrhosis in CHB patients with NAFLD has been previously reported.…”
Section: Discussionsupporting
confidence: 85%
“…Although TE may be affected by several factors, it shows good to excellent performance in CHB patients and decreases the need for LB [13, 27]. Similar to our previous study [28], TE had excellent performance in detecting liver fibrosis and cirrhosis, as revealed by AUCs in the current study. To our knowledge, no comparison between TE and GPR in assessing liver fibrosis and cirrhosis in CHB patients with NAFLD has been previously reported.…”
Section: Discussionsupporting
confidence: 85%
“…There was no significant difference between the two studied groups regarding the degree of liver fibrosis measured by Fibroscan. This was supported by data revealed by Zhang et al, (2019) who performed liver biopsy, Transient Elastography (TE) and Ultrasound for the assessment of steatosis and fibrosis, and concluded that there was no significant correlation between fibrosis and steatosis, and they added that Fibroscan is more accurate than other two methods in the assessment of steatosis and fibrosis [31]. Several previous studies had concluded the same results [9, 32 -36].…”
Section: Discussionmentioning
confidence: 74%
“…In a prior study by Zhang et al used a specific US scoring system including scores for liver contour, liver parenchyma echotexture, hepatic vein contour and spleen size, for assessment of fibrosis in chronic hepatitis B patients with NAFLD, combining US and transient elastography. They showed the combination of the two methods significantly increased the PPV for detection of advanced fibrosis or cirrhosis compared to transient elastography alone; however, the accuracy of diagnosis was not significantly increased 28 . In our cohort combined SN and VCTE resulted in higher specificity and PPV compared to either test alone.…”
Section: Discussionmentioning
confidence: 99%